Women, climate and conflict: What the research tells us - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel highlights how women in fragile and conflict-affected regions experience the sharpest impacts of climate change, from managing households alone to traveling long distances for basic resources and facing heightened risks of violence. At the same time, it challenges common narratives by showing that women are not only victims but also key leaders, farmers, and decision-makers in building resilience. The message calls for greater recognition of women’s roles in climate adaptation and peacebuilding.